การจัดพอร์ตแบบ 10-10-10 - คุณานนต์ ทิศรอด (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
In this project, we design long-term investments in stocks for retirees, Firstly, we choose 10 stocks for minimum-risk portfolios. Then, we model investment in these portfolios by Dollar-Cost Averaging for ten years. Afterwards, we expect 10% dividend since the tenth year of investment. These portfolios are called 10-10-10 portfolios. To minimize the risks, we construct a program utilizing Markowitz’s efficient portfolios method and stocks data from 2002 to 2007. Finally, we test these portfolios with stocks data from 2008 to 2017. The following are our results. (Table)